The institutional conditions of inequality in credential and skill attainment and their impact on occupational placement. (June 2018) - Vogtenhuber, Stefan
Highlights: Family effects on educational outcomes in terms of credentials and skills are large. Occupational placement is influenced more by credentials than by measured skills. Vocational specificity increases educational inequality. Economic coordination mitigates educational inequality while. Coordination increases the effectiveness of skills for occupational placement. Abstract: This study comparatively analyses inequalities in educational outcomes as well as education effects on the occupational status of prime-age workers across 21 countries. Considering two distinct aspects of educational outcomes—credentials and measured worker skills—the study's main role is to assess their partial effects on occupational placement, contingent on social origin. Overall, parental education effects on educational achievement in terms of both credentials and skills are large. Likewise, occupational status is strongly associated with educational certificate attained. Labor market placement based on worker skills is significant as well, but to a lesser extent. The individual-level path dependencies of origin-education and education-destination vary considerably across countries. In part, this variation is associated with a country's skills formation system in terms of vocational specialization and the degree of economic coordination as measured by bargaining coordination. In line with prior research, vocational specificity relates to increased educational inequality. In addition, the study finds that economic coordination mitigates educational inequality as it reduces the intergenerational transmission of certificates and skills. In systems in which vocational specificity is accompanied by a high degree of coordination, the detrimental inequality effect of vocational specificity tends to level off. Moreover, economic coordination facilitates occupational placement based on worker skills. A concise discussion of the policy implications concludes this paper.